Credibility and Exchange Rate Management in Developing Countries - Agenor, Pierre-Richard (IMF Working Papers; Working Paper, 1991)
The paper examines the role of credibility in the conduct of exchange rate policy in developing countries, The analysis is based on a model in which policymakers are concerned about inflation and external competitiveness. Price setters in the nontraded goods sector of the economy adjust prices in reaction to anticipated fluctuations in the domestic price of tradable goods. This type of model is showm to generate a 'devaluation bias' which undermines the credibility of a fixed exchange rate. The effect of reputational factors, signaling considerations, and joining a currency union as possible solutions to this bias is examined.